Clear Cell Myoepithelial Carcinoma of the Upper Lip -A Rare Case Report - Swati GOTMARE; Anish GUPTA; Megha JAIN; Mandavi WAGHMARE (Federation of Turkish Pathology Societies, 2019)
Myoepithelial carcinomas are quite infrequent neoplasms and coupled with their diverse morphological appearance are interesting as far as diagnosis and management is concerned. They account for less than 1% of all salivary gland tumors. The variable morphologic appearance of myoepithelial carcinoma leads to a wide differential diagnosis, including primary salivary gland tumors and metastatic tumors. The prognosis of these tumors is not fair as they are locally aggressive and approximately one third of the patients die of the pathology. We report a case of clear cell variant of myoepithelial carcinoma in an unusual location, i.e. the upper lip. The treatment carried out was wide surgical resection. The patient was followed up for 2 years and was symptom free. The clear cell variant of myoepithelial carcinoma is extremely rare and only about 51 cases of this variant affecting the salivary glands have been reported worldwide so far.